Examine the Effectiveness of Marketing Strategies in Improving Credit Card Adoption: An Empirical Study in Klang Valley - Foo, Yong Sin (2007)
In view of the globalization, Malaysia is opening parts of its services to greater foreign participation. Local banks have gone one round of consolidations and foreign banks expanding its business in local market have made the competition more intense. As the competition rapidly increases, credit card adoption is getting more challenging to marketers, hence effective marketing strategies are important. The theoretical model of the thesis is based on the model of buyer behavior by Kotler and Amstrong (1999). This model is to identify the major factors which influence consumer buyer behavior and how buyer decision process itself affects the buyer behavior. The aim is to examine the effectiveness of marketing strategies in improving credit card adoption. Questionnaire is the selected research instrument in this study to understand what consumers want and how they buy. There are total of 251 respondents participated in the study. The data collected by the survey were analyzed using statistical application, SPSS. It was used to measure the reliability, factor analysis, multiple regression and logistic analysis. The results of the analysis are discussed in the study and the finding revealed that social status is an important factor which affecting customers’ behavior in Klang Valley, they also reacts positively to sales promotions offered in the market. They select products based on their needs’ mainly on product create social admiration. Information search might not be significant to them during decision making process due to several possible reasons. Implications of the study and recommendations in improving credit card adoption are provided.